Modeling Selenium Transport in Saturated Soil Columns: A One-Dimensional Approach - Cong, Wei; Zhang, Xingchang; Feng, Ye (Global Journal of Food and Agribusiness Management, 2024)
The selenium, an essential nutrient and potentially toxic element to human and animal health, is widely used in agriculture and medicine. Soil is the transitional zone through which selenium entered into groundwater. Therefore, the transport of selenium through porous soil is of great environment concern, which is not well understood. The transport of selenite in loessial soil columns was studied using a miscible displacement technique under various flow rates and influent concentrations in this paper. A mathematical model based on one-dimensional convection dispersion equation was formulated to describe the selenium transport. The breakthrough curves with and without tracers were fitted by using the computer program “studio of analytical models”. The results showed that the method without tracer was more accurate than the method with the tracer. Studio of analytical models is a very flexible tool for approximate analysis of one dimensional solute transport problems in soil. The method of parameter estimation using convection-dispersion equation accurately defined the dispersion coefficient and retardation factor from the breakthrough curves and modeled selenite transport through soil. These results suggest that deterministic equilibrium convection-dispersion equation can accurately simulate the breakthrough curves of Se transport in saturated soil and the selection of tracer ions should be cautious when studying the transport of different chemicals.